ADAPTIVE STREAMING OVER HTTP (DASH) UNTUK APLIKASI VIDEO STREAMING - Widyantara, I Made Oka; Bazly, Muhammad Audy; Indra ER, Ngurah (Jurnal Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2015)
This paper aims to analyze Internet-based streaming video service in the communication media with variable bit rates. The proposed scheme on Dynamic Adaptive Streaming over HTTP (DASH) using the internet network that adapts to the protocol Hyper Text Transfer Protocol (HTTP). DASH technology allows a video in the video segmentation into several packages that will distreamingkan. DASH initial stage is to compress the video source to lower the bit rate video codec uses H.26. Video compressed further in the segmentation using MP4Box generates streaming packets with the specified duration. These packages are assembled into packets in a streaming media format Presentation Description (MPD) or known as MPEG-DASH. Streaming video format MPEG-DASH run on a platform with the player bitdash teritegrasi bitcoin. With this scheme, the video will have several variants of the bit rates that gave rise to the concept of scalability of streaming video services on the client side. The main target of the mechanism is smooth the MPEG-DASH streaming video display on the client. The simulation results show that the scheme based scalable video streaming MPEG-DASH able to improve the quality of image display on the client side, where the procedure bufering videos can be made constant and fine for the duration of video views
Keywords: MPEG-DASH, Video Streaming, H.264, HTTP. Internte.